Contentious Politics and Digital Media: Analyzing Effects of Pro-Pti Facebook Contents on Psychological Wellbeing of Users - Khan, Wasif Ali; Bukhari, Seemab Far; Nasir, Tahira (Annals of Human and Social Sciences, 2024)
To investigate the effects of pro-Pakistan Tehreek-e-Insaf (PTI) Facebook content on the psychological well-being of users and explore how users process information and form perceptions in the context of contentious politics. The study is set against the backdrop of contentious politics in Pakistan, where social media has become a significant platform for political discourse. The Elaboration Likelihood Model provides a framework for understanding how users process information and form attitudes. A sample of 200 Pro-PTI Facebook users was selected through purposive sampling and surveyed to examine the effects of exposure to anti-establishment content on their psychological well-being. The findings suggest that exposure to pro-PTI content on Facebook contributes to a trust deficit in the political system and institutions of Pakistan, leading to the formation of stereotypes, perceived realities, and frustration, ultimately affecting users' psychological well-being.